TERRA: A path planning algorithm for cooperative UGV–UAV exploration. (February 2019) - Ropero, Fernando; Muñoz, Pablo; R-Moreno, María D.
Abstract: In this paper, we consider the scenario of exploring a planetary surface with a system formed by an Unmanned Aerial Vehicle (UAV) and an Unmanned Ground Vehicle (UGV). The goal is to reach a set of target points minimizing the travelling distance. Some expected key problems in planetary explorations are the UGVs functionality constraints to reach some target points as a single robot system and the UAVs energy constraints to reach all the target points on its own. We present an approach based on the coordination of a hybrid UGV–UAV system, in which both robots work together for reaching all the target points. Our strategy proposes the UGV as a moving charging station to solve the UAV energy constraint problem, and the UAV as the robotic system in charge of reaching the target points to solve the UGV functionality constraints. To overcome this problem, we formulate a strategy merging combinatorial classic techniques and modern evolutionary approaches aiming to optimize the travelling distance. Our solution has been tested in several simulation runs with different target points distributions. The results demonstrate that our approach is able to generate a coordinated plan for optimizing the hybrid UGV–UAV system in the exploration scenario.